حضور تقنيات السيناريو والسينما في الأعمال القصصية لبشير خلف - بري, حواس; ضريف, اسمهان (جامعة الوادي - University of Eloued, 2022)
تفاعلت القصة القصيرة منذ ظهورها مع فنون أدبية عدةّ؛ كالرواية والمسرح والسينما بتفرعاتها فصارت بذلك فناً منفتحاً على جميع الفنون، حتى تماهت بطابعها الجديد مع تقنيات السيناريو لتحويلها إلى عمل بصري مرئي معتمدًا على أساليبها الفنية والتقنية؛ لذلك جاءت دراستنا هذه تركز على فنية التوظيف السينمائي داخل النسيج القصصي في أعمال "بشير خلف"؛ وذلك بالوقوف على مؤشرات التوازن المزجي لبعض التقنيات الخاصة بالسينما، في محاولة منه لدمج فنين متجاورين بغية خلق فن ثالث يؤسس لترسانة جديدة تعج بالحركية والحيوية المشهدية للصورة السردية. Since its appearance, the short story has interacted with several literary arts; Such as the novel, theater and cinema with its branches, thus it became an open art to all arts, until it became familiar with its new character with scenario techniques to turn it into a visual work based on its artistic and technical methods Therefore, our study focused on the art of cinematic employment within the narrative tissue in the works of Bashir Khalaf; by standing on the indicators of the blending balance of some techniques of cinema, in an attempt to integrate two neighboring arts to create a third art that establishes a new arsenal full of dynamism and scenic vitality of the narrative image
مقال
Keywords: القصة القصيرة، السيناريست، التشكيل البصري، السرد، السينما; short story, scenarist, visual formation, narration, cinema